A theoretical foundation for investigating the spatial economic attributes of airport-centric developments - Mokhele Masilonyane; Geyer Hermanus S. (Bulletin of Geography. Socio-Economic Series, 2021)
Among the various areas of interest on the topic of airports and the geographical distribution of land use, one pertinent theme is the spatial economic analysis of airports and their environs. However, the existing literature predominantly focuses on describing the land-use composition of airport-centric developments, without unpacking the spatial economic forces at play. This gap brings to the fore the need to employ an appropriate theoretical lens to guide the spatial economic analysis of airports and their environs. The aim of this theoretical review paper is thus to identify concepts that are relevant to the analysis of airports and their environs; and to use those concepts to systematically identify the existing theory that is most suitable for investigating the spatial economic forces that drive airport-centric developments. Against the background of globalisation, we scrutinise classical location theories, regional science, growth pole theory and new economic geography against their relational interpretations of the concepts of space, proximity, firm, scale and pattern. Given that it portrays a relational perspective of the aforesaid concepts, the paper concludes that growth pole theory is suitable as the main framework for analysing airport-centric developments. It is therefore recommended that growth pole theory be empirically used to guide the analysis of airports and their environs, and subsequently be used as the basis for developing a theoretical framework tailored for airport-centric developments.